POPULATION DYNAMICS AND ECOLOGY OF FRESHWATER GASTROPODS IN MANCHAR LAKE SINDH, PAKISTAN - S. Saddozai; W. A. Baloch; W. M. Achakzai; N. Memon (Journal of Animal and Plant Sciences, 2013)
The present study is first of its kind that deals with freshwater gastropod populations at Manchar Lake from six selected sampling stations. Gastropods were collected from August 2011 - July 2012. A total of ten species were recorded, these included Bellamya bengalensis, Bellamya naticoides, Thiara tuberculata, Lymnaea acuminata chlamys, Lymnaea acuminata rufescens, Lymnaea acuminata patula, Physa acuta, Gabia arcula, Planorbis exustus and Gyraulus euphraticus. Gastropod population was higher in summer while low population was evident in winter. Various physico- chemical parameters were measured during that period. Minimum average temperature (17.8 oC) was recorded in February, while maximum (34.0oC) in June. Minimum DO was (2.5 mg/l) seen in June, while maximum (7.0 mg/l) in February. Minimum and maximum salinity was (2.2 - 5.9 ppt) in August and June, respectively. The TDS ranged from2101.7 mg/l to 6529.3 mg/l in January and June, respectively. Lowest transparency was (61cm) observed in August, while maximum (124.5cm) in March. Minimum pH (7.6) was recorded in September, while maximum (8.5) in March. Electrical Conductivity ranged from 4.1 mS/cm to 10.1 mS/cm in January and June, respectively. The total hardness was minimum (854mg/l) in September while maximum (1446mg/l) in July. The gastropod population showed a positive correlation with the temperature, TDS, electric conductivity, hardness and salinity. On the other hand pH, transparency and DO showed a negative correlation with population density.
Keywords: gastropod; occurrence; ecology; Manchar Lake